Understanding: Between belief and unbelief - Kahn, Joel S. (The Australian journal of anthropology, 2011)
This paper addresses issues raised in Taylor’s work concerning how communities may come to work in normatively secular ways. For Taylor, it seems to be sufficient for believers (and nonbelievers) to acknowledge that their own ‘construals’ are not shared by everyone. However, this leaves open the question of how the acknowledgement of difference may be turned into respect. A common strategy is to require that faith-based truth claims are ‘bracketed out’, treating secular and religious discourse as ‘nonoverlapping magisteria’. This secularising strategy is, however, problematic on a number of counts. The article makes a case for a less confrontational, more cosmopolitan conversation between secular and religious reason in a postsecular age, examining in particular the possibilities for conversation between science and mysticism. It concludes that it is possible to retain a commitment to naturalism and yet also accept some of the most mystical of propositions, thereby establishing a bridge between ‘secular’ and ‘religious’ forms of reasoning.